High interindividual variability in the CD4/CD8 T cell ratio and natalizumab concentration levels in the cerebrospinal fluid of patients with multiple sclerosis. (27th April 2015) - Harrer, A; Pilz, G; Wipfler, P; Oppermann, K; Sellner, J; Hitzl, W; Haschke-Becher, E; Afazel, S; Rispens, T; van der Kleij, D; Trinka, E; Kraus, J
Summary: Strongly decreased leucocyte counts and a reduced CD4/CD8 T cell ratio in the cerebrospinal fluid (CSF) of natalizumab (NZB)-treated multiple sclerosis (MS) patients may have implications on central nervous (CNS) immune surveillance. With regard to NZB-associated progressive multi-focal leucoencephalopathy, we aimed at delineating a relationship between free NZB, cell-bound NZB, adhesion molecule (AM) expression and the treatment-associated shift in the CSF T cell ratio. Peripheral blood (PB) and CSF T cells from 15 NZB-treated MS patients, and CSF T cells from 10 patients with non-inflammatory neurological diseases and five newly diagnosed MS patients were studied. Intercellular adhesion molecule-1 (ICAM-1), leucocyte function antigen-1 (LFA-1), very late activation antigen-4 (VLA-4), NZB saturation levels, and T cell ratios were analysed by flow cytometry. NZB concentrations were measured by enzyme-linked immunosorbent assay (ELISA). Lower NZB saturation levels ( P < 0·02) and a higher surface expression of ICAM-1 and LFA-1 ( P < 0·001) were observed on CSF CD8 T cells. CSF T cell ratios (0·3–2·1) and NZB concentrations (0·01–0·42 µg/ml) showed a pronounced interindividual variance. A correlation between free NZB, cell-bound NZB or AM expression levels and the CSF T cell ratio was not found. Extremely low NZB concentrations and a normalized CSF T cell ratio were observed in one case. The differential NZB saturation and AM expression of CSF CD8 T cells may contribute to their relative enrichment in the CSF. The reduced CSF T cell ratio appeared sensitive to steady-state NZB levels, as normalization occurred quickly. The latter may be important concerning a fast reconstitution of CNS immune surveillance.